Primary cutaneous CD4+ small‐ to medium‐sized pleomorphic T‐cell lymphoproliferative disorder in a pediatric patient successfully treated with low‐dose radiation. Issue 1 (11th December 2018) - Kim, Esther J.; Aria, Alexander B.; Wilmas, Kelly; Lewis, Daniel J.; Torres‐Cabala, Carlos A.; Nunez, Cesar; Dabaja, Bouthaina S.; Duvic, Madeleine
Abstract: Primary cutaneous CD4+ small‐ to medium‐sized pleomorphic T‐cell lymphoproliferative disorder (PCSM‐LPD) is a rare and low‐grade form of cutaneous T‐cell proliferation with the average age of diagnosis of 54 years. Because of its rarity, the etiology or exact clinicopathology of PCSM‐LPD remains unclear, with < 10 pediatric cases reported. A 13‐year‐old boy presented to our clinic with a raised tumor with PCSM‐LPD histology and was successfully treated with ultra‐low‐dose radiation therapy. While no standard of care has been established for pediatric PCSM‐LPD, this report represents an example of achieving remission in a pediatric tumor with minimal potential for therapy‐related long‐term toxicity.